Patellofemoral Pain in Adolescents: Understanding Patellofemoral Morphology and Its Relationship to Maltracking. Issue 2 (February 2020) - Fick, Cameron N.; Grant, Camila; Sheehan, Frances T.
Background: Developing bone is highly adaptable and, as such, is susceptible to pathological shape deformation. Thus, it is imperative to quantify if changes in patellofemoral morphology are associated with adolescent-onset patellofemoral pain, as a pathway to improve our understanding of this pain's etiology. Purpose: To quantify and compare patellofemoral morphology in adolescent patients with patellofemoral pain with matched healthy adolescent controls and determine if a relationship exists between patellofemoral shape and kinematics (measured during active flexion-extension). Study Design: Cross-sectional study; Level of evidence, 3. Methods: Using 3-dimensional static magnetic resonance images acquired during a previous study, we measured patellar, trochlear, and lateral patellar width; trochlear and patellar depth; Wiberg index; patellar-height ratio; lateral trochlear inclination; cartilage length; and lateral femoral shaft length. Student t test was used to compare shape parameters between adolescents with patellofemoral pain and controls. Pearson correlations and stepwise linear regression models were used to explore the relationship among morphology, kinematics (medial-lateral shift/tilt), and pain. Results: Relative to controls, adolescents with patellofemoral pain had larger sulci (mean ± SD, 6.6 ± 0.7 vs 6.0 ± 1.1 mm; 95% CI, 0.6 mm; P = .043; d = 0.66), lateral patellar width (23.1 ± 2.4 vs 21.4 ± 2.6 mm; 95% CI, 1.6 mm; P = .033; d = 0.70), and patella-trochlear width ratio (1.2 ± 0.1 vs 1.1 ± 0.1; 95% CI, 0.1; P < .001; d = 1.26). Shape correlated with kinematics in both cohorts and in the entire population. In the patellofemoral pain group, lateral shaft length ( r = 0.518; P = .019), Wiberg index ( r = 0.477; P = .033), and patellar-height ratio ( r = −0.582; P = .007) were correlated with medial shift. A moderate correlation existed between patellar-height ratio and lateral patellar tilt ( r = 0.527; P = .017). Half of the variation in patellar shift in the patellofemoral pain cohort was explained by the patellar-height ratio and Wiberg index ( R 2 = 0.487; P = .003). Linear correlations with pain were not found. Conclusion: This study provides direct evidence that patellofemoral morphology is altered and influences maltracking in adolescents with patellofemoral pain, highlighting the multifactorial etiology of this pain. Neither morphology nor kinematics (measured during active flexion-extension) correlated with pain. Both increases and decreases in these parameters likely lead to pain, negating a direct linear correlation.